Abay’s “Words of edification” genre: paradigms of knowledge, understanding and evaluation (Eurasian Journal of Philology Science and Education, 2022)
The article examines the paradigms of knowledge, comprehension, and evaluation of the genre features of the great Kazakh poet Abai Kunanbayev’s “Words of edification”. Abai’s “Words of edification” are an example of a genre of great social, philosophical, cognitive-educational, artistic and aesthetic significance. It is known that the issue of the genre of Abai’s “Words of edification” was the subject of research in the Soviet era and in the period of independence as well. Therefore, in the direction of knowledge, comprehension, evaluation of the genre of Abai’s words of edification, the main goal of analyzing the fund of thoughts accumulated in Abai studies is to re-study many theoretical principles and conclusions, views from the point of view of the modern science achievements, to know, understand, and evaluate deeply in a new way. Therefore, the scientific and practical significance of determining the genre features and poetic values of Abai’s words of edification in the artistic prose model is recognized. In this context, the analysis and conclusions in methodological and theoretical works of the researchers such as M. Auezov, A. Baitursynov, Kh. Suyinshaliyev, R. Syzdykova, Zh. Dadebayev are compared and interpreted in the direction of knowledge, deep comprehension and new assessment of the genre of Abai’s words of edification. The author notes that the paradigms of knowledge, comprehension and evaluation of the genre features of Abai’s words of edification are spread in a new direction during the period of independence, and began to be considered from the point of view of the studies of Anthropology, Creative receptivity, and Hermeneutics. Based on the foundations of Abai studies and genre studies, the secret and character of the diversity of the genre nature of Abai’s “Words of edification” are still in need of new research. As a result of understanding in a new way the paradigms of knowledge, comprehension and evaluation of the genre features of Abai’s “Words of edification” in terms of the achievements of modern science, it is concluded that even if it is a purely artistic prose type, which is in harmony with oral literature, oratorical speech and Oriental models, essayistics, publicistic types, it is an intergeneric type. Analysis of the paradigms of knowledge, comprehension and evaluation of the genre of Abai’s “Words of edification”, their study in an innovative way, and generalization of thoughts on them are considered a contribution to Abai studies. The practical significance of studying the paradigms of knowledge, comprehension and evaluation of the genre of Abai’s words of edification in terms of modern approaches and methodologies is determined. The article has been written within the research project AP08855683 “Scientific foundations and theoretical mechanisms of knowledge, comprehension and application of Abai studies”.